Increasing Salespersons Performance through Performance Evaluation Management in A Book Direct Selling Business Unit (The Indonesian Journal of Business Administration, 2013)
Performance evaluation is probably the most important phase in the salespersons performance management system. Not only the results can be useful for other phases of the system, performance evaluation is the only phase where the salespersons formally can give feedbacks and suggestions to the company and therefore increase their job’s motivation and satisfaction. Increasing the quality of the evaluation process would also increase the performance management, thus increasing the salesperson’s performance. Sygma Daya Insani (SDI) is a book direct selling business unit that was established in 2005, in Bandung. As a direct selling company, the most critical element of SDI business model is its salespersons performance. Final data in 2010 and 2011 show that in average, only 10% of the salespersons made transactions each month. Furthermore, only 1-3% salespersons from all total productive salespersons made transactions every month (12 months) throughout the year for the last two years. All of these describe the low quality of the salespersons’ performance. Therefore, in order to improve its performance, SDI should improve its salespersons performance. The methodology to solve the problem is that the first step is to analyze the SDI corporate performance management. The second step is doing a literature review on salespersons performance evaluation management system. The third step is to formulate a new salespersons performance evaluation management system. This step is divided into 4 phases, a) company’s objectives identification, b) salespersons’ behavior identification, c) formulating a new system, and d) the new system assessment. The final step is formulating the final recommendation of the new salespersons performance evaluation system and its implementation phases. From the problem findings and the result of the questionnaire involving both management and the salespersons, it is concluded that the current salespersons performance evaluation system has the following conditions; a) except for the sales unit, there are no direct relationship between performance and rewards, b) absence of formal discussion of performance objectives and goals between salespersons and their supervisors, c) absence of formal discussion of performance evaluation session, d) performance standards and methods of evaluation were not very well defined, e) no standard criteria to be promoted as a sales supervisor, f) no scheduled time of the evaluation session, and g) no records of the performance evaluation that had been conducted. The proposed method is a combination between Management by Objectives (MBO) and Quantitative and Qualitative Measures. The process is that the organizational purposes are diagnosed and met by joining the sales supervisor and the salesperson in the pursuit of mutually agreed upon goals and objectives and joined to an action plan and then the progress and goal attainment are measured and monitored in appraisal sessions. The concept is expected to be a systematic, relevant, reliable and comprehensive system considering all of the elements and phases of performance evaluation management system in order to facilitate the continuous improvement process of the salesperson. Keywords: performance management, performance evaluation system, direct selling, management by objectives